MEDIA DAN NARASI KESEHATAN: FRAME HARIAN SERAMBI INDONESIA TERHADAP PEMBERITAAN STUNTING DI ACEH - Maulina, Putri; Safrida, Safrida; Nafisah, Raudhatun (Universitas Teuku Umar, 2023)
This article discussed stunting reporting in Aceh within the framework of local media. This study aims to further examine how the local mass media constructs stunting cases in Aceh and how the trend towards emphasizing the reality of stunting is framed in the news texts. The information in this study was derived from daily stunting reports in Indonesia's Serambi region in 2021. The cases of stunting that occurred in Aceh were the subject of this study. The data collection technique was carried out by observing texts on the Serambi Indonesia Daily throughout 2021. There were 37 reports on stunting, and then the researchers selected 12 reports that were deemed relevant and representative of the research problems and themes. From the results of the analysis, two major environmental areas are identified, namely: 1) the Stunting Issues Reporting Map, which has a tendency to discuss the implementation of stunting handling and prevention in Aceh; and 2) the emphasis on resource persons from the point of view of the government and stakeholders involved in stunting prevention. The media coverage frame provides an overview and mapping of information on stunting cases from the government's point of view. As a result, it is recommended that additional research be conducted from the community's perspective as a media audience in understanding and interpreting stunting discourse in Aceh.